Progression of Epiphyseal Cartilage and Bone Pathology in Surgically Treated Cases of Osteochondritis Dissecans of the Elbow. Issue 1 (January 2021) - Takahara, Masatoshi; Maruyama, Masahiro; Uno, Tomohiro; Harada, Mikio; Satake, Hiroshi; Takahara, Daiichiro; Takagi, Michiaki
Background: Although a variety of pathologic conditions associated with osteochondritis dissecans (OCD) have been reported, the pathological progression has remained unclear. Hypothesis: Separation of the immature epiphyseal cartilage is an early event in OCD, and osteonecrosis in the articular fragment is a late event. Study Design: Case Series; Level of evidence, 4. Methods: The participants were 26 boys (mean age, 13.8 years; mean skeletal age score for the elbow, 24.6 points) with capitellar OCD who underwent osteochondral autograft transplantation. A total of 28 cylindrical osteochondral plugs, including the articular fragment, an intermediate layer, and proximal epiphyseal bone, were harvested from the central area of the capitellum and were examined histologically. The articular fragments of OCD were independently assessed by 5 observers and divided into 4 pathological variations: IA, nearly normal-cartilaginous; IB, deteriorated-cartilaginous; IIA, cartilage-ossifying; and IIB, cartilage-osteonecrotic. The reliability of assessment and the correlation of the pathological variations with the clinical data were examined. Results: The reliability of the assessment among 5 observers was almost perfect (Cohen kappa value = 0.91). OCD variations of IA, IB, IIA, and IIB were evident in 5, 10, 5, and 6 patients, respectively. OCD-I (cartilaginous) and OCD-II (osteochondral) corresponded significantly to radiographic stage I (radiolucency or slight calcification with open physis) and stage II (delayed ossification or bony fragment), respectively (Cohen kappa value = 0.79; percentage agreement = 81%). The pathological OCD variations were significantly correlated with the clinical data, including the period from symptom onset to surgery, patient age, and the skeletal age score ( P < .01, in each). Conclusion: The present study has revealed that the pathological variations correspond to the progression of OCD, thus proving our hypothesis. OCD-IA was shown to be an early lesion caused by separation of the immature epiphyseal cartilage. OCD-IB appeared to result from ossification arrest over a prolonged period from the onset of OCD-IA, whereas OCD-IIA showed delayed ossification in the epiphyseal cartilage where vascularization from the surrounding bone had been established. Osteonecrosis in OCD-IIB was shown to be a late pathological event caused by disruption of the vascular supply to OCD-IIA.